Antioxidant activity and flavonoid content of Clusia fluminensis Planch. & Triana - Silva,Maria Carolina A. da (2012)
Clusia fluminensis Planch. & Triana (Clusiaceae Lindl.) is a native species found in regions of high luminosity and water restriction. The aim of this study was to evaluate the antioxidant activity of Clusia fluminensis crude extracts through the scavenging of the stable free radical DPPH, and the determination of flavones and flavonols content in these extracts. The fruit acetonic extract showed the lowest EC50 value (2.71 ± 0.34 g extract / g DPPH), the lowest percentage of remaining DPPH at the concentrations of 125 and 250 µg/mL (about 4% in both), and also the greatest percentage of flavones and flavonols (13.93 ± 0.21 %). Statistical analysis suggests a positive correlation between the presence of flavonoids and the antioxidant activity of this extract. From the obtained results it can be inferred that the acetonic extract of C. fluminensis fruits is an interesting target for the search of substances with antioxidant activity, especially flavonoids.